Economic performance contribute to financial development in Malaysia / Zuriati Saleha Muhamad - Muhamad, Zuriati Saleha (2011)
Relationship between financial development and economic growth has become questioned by many researchers from past research. It been questioned from time to time whether financial development affect economic growth or vice versa. Most of the researchers have their own opinion about the relationship. The primary focus for this study is to identify the relationship between economic growth and financial development in Malaysia. The researcher has focused the data starting from 1990 to 2009 as the researcher want to study the relationship for 20 years. Data are gathered through website such as worldbank.data, BNM and others. Data collected are for economic growth as GDP become the indicator, inflation as CPI becomes the indicator and interest rate. The data being analyzed by using SPSS through multiple regressions, multicollinearity, Durbin Watson, test of significance and test of correlation. From the analysis, the researcher found that there is significant relationship among financial development and economic growth. . As a final point, this study also proposed some valuable information that is useful to others researcher to realize and understand the relationship between financial development and economic growth. Also, by evaluating the recommendations, it is useful for researcher and other parties to assist the current and future potential financial development to conduct better economic growth in future